PERANCANGAN SISTEM INFORMASI AKADEMIK PADA SD MUTUAL 2 KOTA MAGELANG MENGGUNAKAN PHP DAN MYSQL - Kanafi, Kanafi; Sutiyatno, Sukris; Yulmiawati, Yulmiawati (TRANSFORMASI, 2023)
Designing an Academic Information System at SD Mutual 2 Magelang City Using PHP and MySQL " aims to be able to design and build an academic information system that will be applied to Mutual 2 Elementary School Magelang City, and to be able to find out the impact of implementing an academic information system that will be applied to SD Mutual 2 City of Magelang. The research methodology used is the Waterfall method with the stages of the Waterfall method including 1. Requirements Analysis, 2. Design, 3. Development, 4. Testing, 5. Maintenance proposed by Pressman and Maxim (2015). The design used in this method is DFD (Data Flow Diagram), which consists of four main components, namely data input, data output, data storage, and process. The Flow of Document (FOD) is used to describe ongoing procedures. The programming language used is PHP and uses the MySQL database. The results of research conducted by researchers will produce a web-based academic information system that can be used by admin or administration, principals, teachers, staff and students. Management of teacher and staff data as well as student data is managed by the admin or administration while student value data is managed by the teacher.